HIV AND HCV COINFECTION: PREVALENCE, ASSOCIATED FACTORS AND GENOTYPE CHARACTERIZATION IN THE MIDWEST REGION OF BRAZIL - Freitas, Solange Zacalusni; Teles, Sheila Araújo; Lorenzo, Paulo Cesar; Puga, Marco Antonio Moreira; Tanaka, Tayana Serpa Ortiz; Thomaz, Danilo Yamamoto; Martins, Regina Maria Bringel; Druzian, Angelita Fernandes; Lindenberg, Andréa Siqueira Campos; Torres, Marina Sawada; Pereira, Sérgio A.; Villar, Livia Melo; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
A cross-sectional study on prevalence, associated factors and genotype distribution of HCV infection was conducted among 848 HIV-infected patients recruited at reference centers in the Midwest Region of Brazil. The prevalence rate of HIV-HCV coinfection was 6.9% (95% CI: 5.2 to 8.6). In multivariable analysis, increasing age, use of illicit drugs (injection and non-injection), a history of blood transfusion before 1994, and the absence of a steady partnership were significant independent associated factors for HIV-HCV coinfection. The phylogenetic analysis based on the NS5B region revealed the presence of two major circulating genotypes of HCV: genotypes 1 (58.3%) and 3 (41.7%). The prevalence of HIV-HCV coinfection was lower than those reported in studies conducted with HIV-infected patients in different regions of Brazil, due to the fact that illicit drug use is not a frequent mode of HIV transmission in this region of Brazil. Serologic screening of HIV-patients for HCV before initiating antiretroviral treatment, a comprehensive identification of associated factors, and the implementation of effective harm reduction programs are highly recommended to provide useful information for treatment and to prevent HCV coinfection in these patients.